Insights into Medium‐chain Acyl‐CoA Dehydrogenase Structure by Molecular Dynamics Simulations. (8th April 2016) - Bonito, Cátia A.; Leandro, Paula; Ventura, Fátima V.; Guedes, Rita C.
Abstract : The medium‐chain acyl‐CoA dehydrogenase (MCAD) is a mitochondrial enzyme that catalyzes the first step of mitochondrial fatty acid β‐oxidation (mFAO) pathway. Its deficiency is the most common genetic disorder of mFAO. Many of the MCAD disease‐causing variants, including the most common p.K304E variant, show loss of function due to protein misfolding. Herein, we used molecular dynamics simulations to provide insights into the structural stability and dynamic behavior of MCAD wild‐type (MCADwt) and validate a structure that would allow reliable new studies on its variants. Our results revealed that in both proteins the flavin adenine dinucleotide (FAD) has an important structural role on the tetramer stability and also in maintaining the volume of the enzyme catalytic pockets. We confirmed that the presence of substrate changes the dynamics of the catalytic pockets and increases FAD affinity. A comparison between the porcine MCADwt (pMCADwt) and human MCADwt (hMCADwt) structures revealed that both proteins are essentially similar and that the reversion of the double mutant E376G/T255E of hMCAD enzyme does not affect the structure of the protein neither its behavior in simulation. Our validated hMCADwt structure is crucial for complementing and accelerating the experimental studies aiming for the discovery and development of potential stabilizers of MCAD variants as candidates for the treatment of MCAD deficiency (MCADD). Abstract : The medium‐chain acyl‐CoA dehydrogenase (MCAD) is an enzyme that catalyzes the first step of mitochondrial fatty acid β‐oxidation pathway. Herein, we analyzed the structural stability and dynamic behavior of MCAD wild‐type by means of molecular dynamics studies. Our results revealed that the FAD cofactor has an important structural role on the tetramer stability and also in maintaining the volume of the catalytic pockets. We confirmed that the presence of fatty‐acyl substrate changes the dynamics of the catalytic pockets favoring the reaction mechanism.